Two Different Faces of Representation: A Comparative Analysis of the Classical Dalalat Conception and the Concept of Modern Semiosis in the Context of Definition and Its Elements - ÖNDER, ŞEYMA GÜLSÜM (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2021)
In classical logic, ad-dalalat, which means that knowledge of one thing requires knowledge of another, has an important place in Islamic sciences. On the other hand, semiotics has developed in a structure that concerns many fields from thought to art and from science to culture since its establishment. Semiosis, which is used as one of the basic terms of science branches such as semiotics and narratology with its sub-branches, was put forward by the logician philosopher Charles Sanders Peirce (1839-1914). In short, semiosis is the name given to the process of representing a certain thing (object) on a certain ground, in a certain meaning. In this article, the main difference between the terms dalalat and semiosis, which are evaluated under the phenomenon of representation, will be revealed based on the definitions given to these terms in their own fields of existence and the knowledge of the elements. Accordingly, in the introduction, the place of dalalat in Islamic tradition in general and classical logic in particular will be briefly mentioned. In the first part, dalalat will be discussed with its definition and elements, while in the second part, Peirce's semiotics and the concept of semiosis will be discussed by briefly giving modern semiotics' schools. In the third chapter, a comparative analysis of classical dalalat and semiosis' terms will be made, taking into account the ground that played a role in their formation. As a result, it will be pointed out that the relationship between the emergence ground of the dalalat and the elements it contains is mind-centred and based only on the dal-medlul relationship, while the modern concept of semiosis is object- oriented and is knitted with a network of double and triple relations between the sign, the object and the mind. Therefore, it will be pointed out that the semiosis reflects the concept of representation better than the dalalat in terms of the breadth of its scope, apart from the limitation imposed by its object-oriented nature.
Keywords: Semiotics; Logic; Peirce; Object; Relation of Signifier-Signified